2021
DOI: 10.1155/2021/4496488
|View full text |Cite
|
Sign up to set email alerts
|

Chest X-Ray Findings in COVID-19 Patients Presenting to Primary Care during the Peak of the First Wave of the Pandemic in Qatar: Their Association with Clinical and Laboratory Findings

Abstract: When managing coronavirus disease 2019 (COVID-19) patients, radiological imaging complements clinical evaluation and laboratory parameters. We aimed to assess the sensitivity of chest radiography findings in detecting COVID-19, describe those findings, and assess the association of positive chest radiography findings with clinical and laboratory findings. A multicentre, cross-sectional study was conducted involving all primary health care corporation-registered patients (2485 patients) enrolled over a 1-month … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 26 publications
0
10
0
1
Order By: Relevance
“…Cai et al and Dong et al reported that atypical presentations of COVID-19 occur in older adults and in people with medical comorbidities who may experience more respiratory symptoms and fever than those who are younger or do not have comorbidities [ 27 , 28 ]. Moreover, Abougazia et al reported that patients with diabetes, cardiac disease, hypertension, obesity, and chronic kidney disease were at a higher risk of positive chest X-ray findings [ 29 ]. Alguwaihes et al found that, among the 439 COVID-19 patients who were included in their study, the most prevalent comorbidity was vitamin D deficiency (74.7%), followed by diabetes (68.3%), hypertension (42.6%), and obesity (42.2%) [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cai et al and Dong et al reported that atypical presentations of COVID-19 occur in older adults and in people with medical comorbidities who may experience more respiratory symptoms and fever than those who are younger or do not have comorbidities [ 27 , 28 ]. Moreover, Abougazia et al reported that patients with diabetes, cardiac disease, hypertension, obesity, and chronic kidney disease were at a higher risk of positive chest X-ray findings [ 29 ]. Alguwaihes et al found that, among the 439 COVID-19 patients who were included in their study, the most prevalent comorbidity was vitamin D deficiency (74.7%), followed by diabetes (68.3%), hypertension (42.6%), and obesity (42.2%) [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“… 16 Radiological imaging complements clinical evaluation and laboratory parameters for managing COVID-19 patients. 17 Therefore, categorizing patients into severe or non-severe becomes more defined, allowing for earlier interventions and decisions of hospital admission. Although CRP and D-dimer have been reported to correlate with poor outcome, the higher costs of CPR and D-dimer examination has resulted in significant pressure on the healthcare system.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with higher COVID-19 computer tomographic scores were more likely to suffer from severe and critical diseases. [38,39] In the present study, patients with abnormal chest X-ray findings, presence of consolidation, and more prominent ground glass opacities manifestations mostly belonged to the more ill therapeutic anticoagulation groups (TA and TAA).…”
Section: Discussionmentioning
confidence: 52%